EU: the Debate about the Integrational Paradigm and the Problems of the Eastern Expansion - Georgiev, Andrei (Research Papers, 2007)
The eastwards enlargement of the EU (EU-10+2) is shown in its dual function: as a source for conflicts and as a motive for reconsidering of the basic principles of the European integration project. We see focused the problems of the common market, the budget reform, internal and external competition, post-industrial and “catching-up” development. The theme for the limits of the enlargement of the EU is explored. The character, the depth and the direction of the current changes in the EU, the dilemmas and possibilities of EU-10+2 in this context are discussed.